Applications of the Premack Principle: A Review of the Literature. Issue 1 (January 2023) - Herrod, Jessica L.; Snyder, Sara K.; Hart, Joseph B.; Frantz, Sarah J.; Ayres, Kevin M.
The Premack principle states that any Response A can reinforce any other Response B if the independent rate of A is greater than the independent rate of B. This theory demonstrates reinforcer relativity, where the relative probabilities of responses can be more impactful than preference. Applying the Premack principle involves arranging the environment to restrict access to certain responses based on relative probabilities of a set of given responses. Though the Premack principle is described in modern behavior analytic texts, Konarski et al. identified a lack of empirical evidence to support its application. The purpose of the current paper is to systematically review the extant literature using the Premack principle and evaluate how and if researchers have applied reinforcer relativity as described by Premack and the subsequent effectiveness of these procedures. Additionally, we make recommendations for practitioners and future researchers based on our findings.